2010
DOI: 10.1007/s00126-010-0298-3
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of sediment-hosted stratiform copper–cobalt mineralization at Luiswishi and Kamoto, Katanga Copperbelt (Democratic Republic of Congo)

Abstract: The sediment-hosted stratiform Cu-Co mineralization of the Luiswishi and Kamoto deposits in the Katangan Copperbelt is hosted by the Neoproterozoic Mines Subgroup. Two main hypogene Cu-Co sulfide mineralization stages and associated gangue minerals (dolomite and quartz) are distinguished. The first is an early diagenetic, typical stratiform mineralization with finegrained minerals, whereas the second is a multistage synorogenic stratiform to stratabound mineralization with coarse-grained minerals. For both sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 86 publications
4
42
1
Order By: Relevance
“…S CDT values ranging from +11.1 to 17.5‰ (average +15.97‰; Xu et al, 2009), comparable to a mean δ 34 S value of +17.5‰ ± 3‰ for Neoproterozoic seawater at the time of deposition of the Shilu Group, but distinctly different from those of the Zambian Copperbelt (El Desouky et al, 2010;Sweeney et al, 1986). Nevertheless, the previous study (Xu et al, 2013) has indicated that the tectonic, metamorphic and hydrothermal reworking which most likely was related to the multistage orogenies in South China has significantly modified the Shilu district resulting in enrichment and upgrading of Fe-and Co-Cu ores and secondary mineralization.…”
mentioning
confidence: 98%
“…S CDT values ranging from +11.1 to 17.5‰ (average +15.97‰; Xu et al, 2009), comparable to a mean δ 34 S value of +17.5‰ ± 3‰ for Neoproterozoic seawater at the time of deposition of the Shilu Group, but distinctly different from those of the Zambian Copperbelt (El Desouky et al, 2010;Sweeney et al, 1986). Nevertheless, the previous study (Xu et al, 2013) has indicated that the tectonic, metamorphic and hydrothermal reworking which most likely was related to the multistage orogenies in South China has significantly modified the Shilu district resulting in enrichment and upgrading of Fe-and Co-Cu ores and secondary mineralization.…”
mentioning
confidence: 98%
“…Bartholomé et al, 1972). This replacement of pyrite by chalcopyrite is followed by the replacement of chalcopyrite by bornite, bornite by digenite and finally digenite by chalcocite (El Desouky et al, 2010). Chalcopyrite, bornite and chalcocite can also occur as direct precipitates or replacement of anhydrite in nodules and lenses (Muchez et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This early pyrite was replaced by chalcopyrite (Bartholomé et al, 1972). At Kamoto and Luiswishi (Katanga Copperbelt), this replacement is followed by a general succession of chalcopyrite, bornitecarrollite and chalcocite (El Desouky et al, 2010). A vertical and lateral distribution pattern from copper-rich minerals (chalcocite) to pyrite has been described for many deposits in the Katanga Copperbelt (Oosterbosch, 1962;Lefebvre, 1989;Cailteux et al, 2005).…”
Section: Geological and Geochemical Constraints On Copper Mineralizationmentioning
confidence: 95%
See 1 more Smart Citation
“…2B). The interaction between the oxidized Cu-bearing brines and reduced carbonaceous shales would have resulted in the oxidation of organic matter El Desouky et al, 2010), which may be the main reason for the significant variation of carbon isotope values.…”
Section: Interpretation Of Carbon and Oxygen Isotopesmentioning
confidence: 99%